Jacques LEZRA, "Untranslating Machines: A Genealogy for the Ends of Global Thought". Nueva York, Rowman & Littlefield, 2017, 222 pp. - Valls Boix, Juan Evaristo (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
Review of Jacques Lezra, Untranslating Machines: A Genealogy for the Ends of Global Thought. Nueva York, Rowman & Littlefield, 2017, 222 pp.
Keywords: Untranslatable; Deconstruction; Philosophizing in languages; Materialism